Bereszith by Harry Duda against the background of the Polish tradition of translating the Book of Genesis - Nowak, Małgorzata (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
The article discusses the poetic rendering of the Book of Genesis: Bereszith, czyli Księga Rodzaju (Genesis) wierszem przez Harry’ego Dudę [Bereszith, or the Book of Genesis in Verse by Harry Duda] (Lublin 2017). Following his own translation strategy worked out for his other biblical translations, in his Bereszith, Duda employs rhymed poetry. The formal organization of the poem is that of quatrain with the ABAB rhyme scheme and the regular Polish alexandrine metrical line. The poetic language of Harry Duda’s Book of Genesis is accurate and thorough; bookish in a general perception. His stylistic solutions can at times be questionable (vernacular and dialectal word choice, some items of rare or specialist kind). These forms mostly occur in the rhyming endings of the lines and their presence need to be seen as imposed by the adopted rhyming strategy; Although the poet declares his use of „relatively contemporary language style”, his work unveils historically marked lexical and grammatical items, which add to the elevation and the tarnish of a biblical text in translation.